PERAN KEMARITIMAN INDONESIA DI MATA DUNIA - Harries Arizonia Ismail; Erawati Kartika (UNIMAR AMNI Semarang, 2019)
The purpose of choosing this study is to examine Indonesia's vision as a world maritime axis. This vision is very important because it is nominated by President Joko Widodo in the speech on the official opening of the 2018 Our Ocean Conference (OCC) event in Nusa Dua, Bali, Monday (10/29/2018). This vision is becoming more important since Indonesia still encountered by maritime problems, such as security and financial issues, which are suspected to be attaching that vision. This study is using heuristic and eclectic methods. This is a descriptive qualitative philosophical study that will be centered on the President's speech and the reporting of national newspapers on maritime issues, which have the opportunity to raise nation and state ethical issues. Realizing that Indonesia's vision as a global maritime axis must be coming true in order to format Indonesian roles on maritime subject in the eye of the world.Keywords : Maritime; Indonesia world maritime axis, Our Ocean Conference heuristic, Eeclectic, Philosophical study Tujuan penulisan ini adalah untuk mengkaji visi Indonesia sebagai poros maritim dunia. Visi ini begitu penting karena dipidatokan oleh bapak Presiden Joko Widodo dalam rangka pembukaan resmi ajang Our Ocean Conference (OCC) 2018 di Nusa Dua, Bali, Senin (29/10/2018). Visi ini semakin penting ketika masih banyak dijumpai problem kelautan kita, seperti masalah keamanan dan perekonomian yang ditengarai akan melemahkan visi tersebut. Melalui metode heuristis dan eklektik, kajian filosofis berjenis deskriptif kualitatif ini akan berpusat pada pidato Presiden dan pemberitaan surat kabar nasional tentang problem kemaritiman, yang berpeluang memunculkan problem etis berbangsa dan bernegara. Hasilnya, visi Indonesia sebagai poros maritim dunia harus tetap diwujudkan demi terwujudnya peran kemaritiman Indonesia di mata dunia.Kata kunci : Kemaritiman, Indonesia poros maritim dunia, Our Ocean Conference, Heuristis, Eklektik, Kajian filosofis